A REPLENISHMENT POLICY FOR ITEM WITH PRICE DEPENDENT DEMAND AND DETERIORATING UNDER MARKDOWN POLICY - Hui Ming Wee; Gede Agus Widyadana (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2007)
Many researches on deteriorating inventory model have been developed in recent years. This paper develops deteriorating inventory model with price-dependent demand and uses markdown policy to increase profit. Two examples are used to explain the model and some interesting results are derived. Markdown policy can increase total profit, but the best markdown time and price depend are case dependent.